Porto Rican Delegation to the United States - Todd, Roberto H. (My University, 1924)
Porto Rican delegation to the United States to the honorable the president, and senate and House of representatives of the United States in congress Assembled.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.